Kajian Status Sosial Ekonomi Keluarga dalam Pemilihan Asuransi Kesehatan - Dwi Noerjoedianto; Andi Subandi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
Health insurance is a health financing guarantee that needs to be chosen to face health risks and increasingly expensive medical costs.  Socio-economic status is related to the level of ability that a person has in buying health services. Currently, 68.25% of the population who have compulsory health insurance (BPJS Kesehatan, Jamkesda and Company Insurance) have voluntary insurance and 1% have voluntary insurance. The purpose of this study was to determine the relationship between family socioeconomic status and the choice of health insurance in Jambi City. The research design was a cross sectional survey method with a population of 183,448 households focusing on a sample of 164 households, the sampling technique was probability sampling. Analysis with Chi-Square test, shows that there is a relationship between education (pv= 0.021) on the choice of health insurance and there is no relationship between income (pv=0.324), occupation (pv=0.644), number of family members (pv=0.377),   and asset ownership (pv=0.063) on the selection of health insurance.